DOMESTIC ARBITRATION LAW FOR ALTERNATIVE RESOLUTION OF DISPUTES PERFORMANCE IMPROVEMENT PROSPECTS (Academia Science Repository, 2023)
In the conditions of modernization and reform of our country, the ongoing reforms in the law enforcement and judicial-legal spheres are aimed primarily at the comprehensive protection of human rights, freedoms and legitimate interests. Providing the State with the role of the main reformer, ensuring the rule of law, and conducting a strong social policy represent reforms that are being implemented gradually and gradually. It should be noted that today, in addition to competent courts, Domestic Arbitration Law face various problems when considering a number of cases on civil and economic disputes in the manner of alternative dispute resolution. This article explores the issue of prospects for improving Domestic Arbitration Law in resolving disputes in an alternative manner.